The effect of self-efficiency, emotional intelligence, and spiritual intelligence on performance of education services and culture of merangin district - Askar Jaya; Anggi Selvianti Wulandari; Fauzan Kurnia Arivia Depari; Sudarna Sudarna (Education and Social Sciences Review, 2022)
This study aims to see the effect of (1)Self-efficacy on the performance of employees of the Merangin Regency Education and Culture Office. (2)Emotional Intelligence on the performance of the Merangin Regency Education and Culture Office employees. (3)Spiritual intelligence on the performance of employees of the Merangin Regency Education and Culture Office (4)Self efficacyemotional intelligence and spiritual intelligence jointly affect the performance of the Merangin Regency Education and Culture Office employees. The population in this study is allThere are 49 employees of the Merangin Regency Education and Culture Office. And the technique of determining the number of samples taken as respondents with the technique of taking this sample using the total sampling technique (whole sample). Total sampling is a sampling technique where the number of samples is the same as the population. The reason for taking total sampling is because the total population is less than 100 and the entire population is used as a research sample. The results of this study indicate that (1)Self efficacyprovide a positive influence on the performance of employees in the Department of Education and Culture of Merangin Regency. (2)Emotional intelligenceprovide a positive influence on the performance of employees in the Department of Education and Culture of Merangin Regency. (3)Spiritual intelligencegive a positive influence on the performance of employees in the Department of Education and Culture of Merangin Regency (4)Self-efficacy, emotional intelligence, spiritual intelligence jointly has a positive effect on the performance of the Merangin Regency Education and Culture Office employees.